Free-Living and Plankton-Associated Vibrios: Assessment in Ballast Water, Harbor Areas, and Coastal Ecosystems in Brazil - G. Rivera, Irma N.; Souza, Keili Maria C.; Souza, Claudiana P.; Lopes, Rubens M. (Frontiers in Microbiology, 2013)
Ballast water is a major transport vector of exotic aquatic species and pathogenic microorganisms. The wide-ranging spread of toxigenic Vibrio cholerae O1 from harbor areas has been frequently ascribed to discharge of contaminated ballast water into eutrophic coastal environments, such as during the onset of the seventh cholera pandemic in South America in the early 1990s. To determine the microbiological hazards of ballast waters transported to Brazilian ports, we evaluated water and plankton samples taken from (i) ballast water tanks of recently arrived ships, (ii) port areas along the Brazilian coastline from ~1 to 32 oS and (iii) three coastal areas in São Paulo State. Vibrio concentration and toxigenic V. cholerae O1 occurrence were analyzed. Plankton-associated vibrios were more abundant than free-living vibrios in all studied environments. Vibrio cholerae was found in 9.5% of ballast tanks and 24.2% of port samples, both as free-living and attached forms, and was absent off São Paulo State. Toxigenic V. cholerae O1 isolates (ctxA+, tcpA+), involved in cholera disease, were found in ballast water (2%) and harbor (2%) samples. These results confirm that ballast water is an important carrier of pathogenic organisms, and that monitoring of vibrios and other plankton-attached bacteria is of paramount importance in ballast water management programs.